PROBLEMS OF POSTGRADUATE TRAINING ORGANIZATION ON THE BASIS OF THE FEDERAL STATE EDUCATIONAL STANDARDS OF THE THIRD LEVEL OF HIGHER EDUCATION - Vasiliy S. Senashenko (Высшее образование в России)
The article discusses the perspectives of postgraduate training programs which received the status of the third level of higher education. The problems of postgraduate training organization and development in the new conditions are considered. The aim of postgraduate education modernization is to supply scientific and education organizations with highly qualified personnel inasmuch science and education now experience personnel shortfall. The new federal law "About Education in the Russian Federation" regards postgraduate education as the third level of higher education. A new model of doctoral training is designed to recover the production both of research specialists and university teaching staff. The author proposes to divide the doctoral training programs into two stages: the first includes the educational component and master's thesis preparation, and the second stage includes the research component and preparation and defense of doctoral thesis. Organization of doctoral training in new conditions requires the extension of a list of graduates' activities. The author argues that changing of doctoral training status can result in loss of quality of the research component of the domestic system of preparation of highly educated workers (researchers and university teaching staff).